Characterizing the Dissolved Organic Matter (DOM) Leached from Avicennia alba Leaves Using Fluorescence Excitation-Emission Matrix (FEEM) Spectroscopy - Suksomjit, Marut; Yamsomphong, Kanokwan; Chuaybumrung, Koonlagarn; Supawanich, Natcha; Vichkovitten, Tritep (Burapha Science Journal, 2026)
Dissolved Organic Matter (DOM) has an important role in aquatic ecosystems. However, role of DOM is depended on its characteristics. This study investigated the characteristics of leached DOM from Avicennia alba leaves using FEEM spectroscopy technique. The results showed that the characteristic of DOM derived from two ages leaves (yellow and green leaves) are similar. Tannin was the major component in all leached DOM samples which differed from other mangrove species. This might affect to the roles of DOM that derived from mangrove leaf litter of each species in the bioavailability and geochemical cycling in the environment. For DOM production, yellow leaf derived higher amount of DOM than green leaf.